Co‐Cluster‐Based Metal–Organic Frameworks as Selective Catalysts for Benzene Tandem Acylation–Nazarov Cyclization to Benzocyclopentanone. Issue 6 (18th December 2017) - Liu, Mengjia; Gao, Kuan; Fan, Yanru; Guo, Xiaoqing; Wu, Jie; Meng, Xiangru; Hou, Hongwei
Abstract: One‐step selective benzene acylation–Nazarov cyclization is an attractive, yet challenging method for the synthesis of the benzocyclopentanone skeleton, which is key intermediate of many natural products. Herein, two metal‐cluster‐based metal–organic frameworks (MCOFs) (H3 O)2 [Co4 (pbcd)2 (μ3 ‐OH)2 ]⋅ CH3 CH2 OH⋅ 4 H2 O n (1 ; pbcd=9, 9′‐(propan‐1, 3‐diyl)bis(9 H ‐carbazole‐3, 6‐dicarboxylic acid) and [Co5.25 (mcd)2 (HCO2 )(μ2 ‐O)0.5 (μ3 ‐OH)0.5 (H2 O)4 ]⋅ 6 H2 O⋅ 5 DMF n (2 ; mcd=9, 9′‐methylenebis(9 H ‐carbazole‐3, 6‐dicarboxylic acid) were developed to catalyze a tandem Nazarov cyclization reaction of 1, 3‐dimethoxybenzene with α, β‐unsaturated carboxylic acids for the synthesis of cyclopentenone[ b ]benzenes. MCOFs1 and2, which were constructed from tetranuclear Co II cluster [Co4 (μ3 ‐OH)2 ] and hexanuclear Co II cluster [Co6 (HCO2 )(μ2 ‐O)(μ3 ‐OH)], respectively, exhibit high catalytic activity arising not only from their suitable channel size and accessible catalytic sites, but also because of their high density of Lewis acidic sites within the frameworks and the synergic activity among Co II ions. In contrast, [Co2 (pbcd)(bpe)]⋅ 2 H2 O⋅ 2 DMF n (3 ; bpe=1, 2‐bis(pyridin‐4‐yl)ethane) containing binuclear Co II and having large pore windows is a highly selective catalyst for obtaining exclusively the acylation products. Easy product separation, simple reaction procedures, and catalyst recycling make the catalyst system attractive. This work highlights the synergistic effect among ions of MCOFs in interacting with substrates in a sequential or cooperative manner to achieve tandem catalysis. Abstract : In the frame : Two metal‐cluster‐based metal–organic frameworks (MOFs) were synthesized and used as heterogeneous catalysts to selectively catalyze tandem acylation–Nazarov cyclization reactions of 1, 3‐dimethoxybenzene with α, β‐unsaturated carboxylic acids for the synthesis of cyclopentenone[ b ]benzenes. In contrast, a MOF based on binuclear units is a highly selective catalyst for obtaining the acylation product (see scheme).